2017
DOI: 10.4172/0976-4860.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xanthan Gum and Carboxymethyl Cellulose on Physical Properties of Cream Cheese

Abstract: Many problems originated from consuming the high fat products, so reducing the fat in foods is very attractive field. In this study, the effect of xanthan gum at levels 0.05%, 0.17%, 0.3% and carboxymethyl cellulose at 0.02%, 0.11%, 0.2% on physical properties of cream cheese was studied. Results showed that samples contain xanthan and CMC had significant differences (p<0.05) in terms of textural properties in comparison to control. We found that increase the level of gum in samples were decreased the adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…Generally, gumminess has increased with an increase fat content. Similar results were obtained Salari et al (2017). Except for fat, total solids, moisture, protein to moisture ratio can affect on texture characteristics of cheese (Salari et al, 2017).…”
Section: Textural Propertiessupporting
confidence: 80%
“…Generally, gumminess has increased with an increase fat content. Similar results were obtained Salari et al (2017). Except for fat, total solids, moisture, protein to moisture ratio can affect on texture characteristics of cheese (Salari et al, 2017).…”
Section: Textural Propertiessupporting
confidence: 80%
“…They reported that the addition of xanthan gum enhanced the protein matrix's ability to bind water, suggesting that changes in the pressure of the protein matrix were likely the cause of the cheese's decreased hardness. However, Salari et al (2017) found that the cream cheese treatments with the highest fat content and the lowest amount of xanthan gum had the highest hardness.…”
Section: Textural Characteristics Of Cheese Analoguesmentioning
confidence: 95%
“…Cheese-containing carboxymethyl cellulose (S5) had the highest gumminess values (P ≤ 0.05) followed by xanthan cheese (S6) while cheese made with the commercial stabilizer Hitex 555(S7) had the least values. Cheese gumminess has been shown to correlate positively with the level of added carboxymethyl cellulose and xanthan gum to cream cheese [36]. The order of gumminess values for experimental cheeses was in the order carboxymethyl cellulose > xanthan > native starch > Dairy gel 161 stabilizer > carrageenan > guar gum > modified starch > Hitex 555, respectively.…”
Section: Textural Attributesmentioning
confidence: 99%